#TITLE_ALTERNATIVE# - SASTRAATMAJA (NIM 10503038), ARMAN
Stripping voltammetry for heavy metal analysis has a very good sensitivity. Mercury-based electrodes has been proved to have a good selectivity and sensitivity in stripping voltammetry. To reduce the use of mercury in analysis, a new alternative of mercury-based electrodes must be develop. Bismuth film electrode have been proposed as an alternative of mercury-based electrodes in voltammetric analysis. This electrode is environmental friendly and has low toxicity. In this research bismuth film electrode were prepared by coating bismuth onto a copper substrate surface with in situ and ex situ electrodeposition. The electrodeposition process was conducted acetic buffer supporting electrolyte (pH 4.5) with deposition potential of -1.0 V, -1.2 V and -1.4 V. Potential window for in situ and ex situ analysis are -1.4 to 0 V and -1.4 to -0.3V, respectively. Analysis was conducted with anodic squarewave stripping voltammetry technique. The detection limit of this measurement were 40.09 μg l-1, 25.25 μg l-1 and 50.14 μg l-1 at deposition time 300 s for Pb2+, Cd2+ and Zn2+, respectively. This research provides the possibility of using copper bismuth film electrode as alternative electrode for heavy metal analysis.